FACTORS CAUSING DIVORCE FOR OLD AGE COUPLES IN SOCIETY - Sofyan, Akhmad; Yatul, Robi (Fasya UIN Sultan Aji Muhammad Idris Samarinda, 2023)
Old age is an age that is very vulnerable to disputes between husband and wife which sometimes just because of trivial things, the two partners will be at odds and some will even cause fights. According to the researchers' observations that there was a divorce in Kota Bangun District where the age of the couple was no longer young. This raises the question, what are the factors contributing to the divorce and how does the impact of divorce affect the two partners? This study uses qualitative research with an empirical normative approach. The results of the research conducted showed that the causes of divorce that occurred for old couples in the Kota Bangun sub-district were caused by financial problems and because the husband was unable to provide all of the income he earned to his wife, causing suspicion for the wife. In addition, disputes are also caused by problems in sexual relations where one party has no desire to have sexual intercourse. And the last one is caused by differences in religious views which have an impact on the emergence of differences in parenting and educating children and this has been buried for years. Then the negative impact that arises as a result of divorce that occurs in old couples is that one partner experiences inner burden and depression because they feel they have failed in building a household. Besides that, it will also cause hostility and discomfort when meeting with ex-spouse or relatives of the former partner. Likewise for children who are still in their teens will experience emotional instability because they see their parents separate. But there is also a positive impact, namely the end of prolonged disputes and both partners will both examine themselves so that they become better individuals.